Marital Horizon: Studi Komparatif pada Dewasa Awal dengan Orang Tua Bercerai dan Utuh - Fitri Andriyani; Langgersari Elsari Novianti (Psympathic : Jurnal Ilmiah Psikologi, 2021)
This study aims to compare the views of adolescents with divorced and complete parents on marriage. Using comparative method, the view on marriage was measured by marital horizon with additional open questions on learned criteria from parents' marriage. Through convenience sampling, the participants recruited were 319 adolescents aged between 21 and 28 years old live in Bandung with condition of divorced parents and complete parents. The descriptive analysis and Mann Whitney test show that there are differences on prioritizing marriage and the ideal age to get married. However, there is no differences on ideal age differences in marriage and criteria that should be prepared before marriage. Also, this study found religious affiliation as a criterion that should be prepared marriage and it is what they learned from their parents' marriage.